Efficacy and safety of fenofibrate add-on therapy in patients with primary biliary cholangitis refractory to ursodeoxycholic acid: A retrospective study and updated meta-analysis - Xuan Guoyun; Ding Dawei; Liu Ning; Hu Yinan; Yang Fangfang; Tian Siyuan; Sun Hao; Yang Jiaqi; Xu Ang; Guo Guanya; Chen Xi; Shang Yulong; et al. (Frontiers Media S.A., 2022)
Background: Ursodeoxycholic acid (UDCA) is currently used for the treatment of primary biliary cholangitis (PBC), but some people do not respond well to UDCA. It reported that the combination of fenofibrate and UDCA can improve the clinical indices in these patients. However, more high-quality evidence is needed to improve guideline recommendations.Methods: Through an updated meta-analysis, studies included were valued by the Cochrane Evaluation Manual and Robins-I. Biochemical and clinical indicator changes in UDCA-refractory PBC patients receiving combination therapy were analyzed by Revman 5.42. Then, we explored the influence of fenofibrate dose and the effectiveness and safety of long-term application by retrospective cohort study.Results: Our meta-analysis included nine publications with a total of 389 patients, including 216 treated with UDCA alone and 173 who received combination therapy. The meta-analysis showed that combination therapy was more effective than UDCA monotherapy in decreasing biochemical parameters, such as ALP, GGT, IgM, and TG. However, the occurrence of pruritus and adverse events was slightly higher with combination therapy than with UDCA monotherapy. A total of 156 patients were included in our cohort study: 68 patients underwent UDCA monotherapy, and 88 patients underwent combination therapy. Among UDCA-refractory patients, fenofibrate add-on therapy significantly improved the ALP normalization rate.Conclusion: The combination of fenofibrate and UDCA can decrease biochemical parameters, of UDCA-refractory PBC patient. Furthermore, the efficacy and safety of long-term combination therapy were also confirmed in our cohort study.